The Influence Of Competence And Job Analysis On Employee Performance With Career As An Intervening Variable At The Office Of The Department Of Education And Culture Of Medan City - Imelda Tomusari Margaretha Silaban; Muhammad Toyib Daulay; Saimara A.M Sebayang (Cattleya Darmaya Fortuna, 2026)
This study aims to examine the effect of competence and job analysis on employee performance with career development as an intervening variable at the Department of Education and Culture Office of Medan City. This research employs a quantitative approach with an associative research design. The population consists of all employees of the Department of Education and Culture Office of Medan City totaling 133 people, and the entire population is used as the sample through a saturated sampling (census) technique. Data were collected through questionnaires, observation, and documentation, while data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results show that: (1) competence has a positive and significant effect on career development and employee performance, (2) job analysis has a positive and significant effect on career development and employee performance, and (3) career development acts as a mediating variable that strengthens the effect of competence and job analysis on employee performance. Based on these findings, it is recommended that management improve employee competence and the quality of job analysis, as well as optimize career development programs to enhance overall employee performance.